The Governance of Local Communities : Global Perspectives and Challenges (Nova Publishers, 2017)
The quality of local governance matters more than ever before. To many citizens, their local government is the most tangible form of government, and it is also the layer of government with which they have most contact in their everyday life. The power of the local administration is that it represents ordinary citizens. People eat, drink, work, play and socialize with others in towns and cities. To be fully effective, local government management and service delivery capacity needs to be strong, and resources need to be adequate. Civil society and businesses are essential actors in ensuring local governments have the capacity to meet the needs of its citizens.